(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
The purpose of this article is to develop a program of preparation for Responsible competitions through the rational planning of training loads at the stages of many years of preparation of qualified wrestlers engaged in wrestling. The volume of downloads was given, which varied in the preparatory stages of the wrestlers. In this case, the level of indicators was determined, the norms of the volume of downloads were established. The norms of load capacity were determined in combination with such descriptions as the task of training, the direction of loads for the day of training (rapid normalization) macrocycle (daily normalization), as well as specialization. In order to increase the volume of training, the wrestlers of the experimental group used the developed norms of the volume of downloads for rapid and daily normalization, and also used the combination of load in the direction of guidance in training macrocycles. By us, it was introduced into the study as a training program developed by identifying and evaluating the many years of training invasions of athletes. The condition of the wrestlers up to the stages of many years of training was determined, and the planning and preparation program of training loads optimized for the period of training qualified wrestlers was developed and allowed to win responsible competitions.